Novel Anti-fibrotic Therapies - McVicker, Benita L.; Bennett, Robert G. (Frontiers in Pharmacology, 2017)
Fibrosis is a major player in cardiovascular disease, both as a contributor to the development of disease, as well as a post-injury response that drives progression. Despite the identification of many mechanisms responsible for cardiovascular fibrosis, to date no treatments have emerged that have effectively reduced the excess deposition of extracellular matrix associated with fibrotic conditions. Novel treatments have recently been identified that hold promise as potential therapeutic agents for cardiovascular diseases associated with fibrosis, as well as other fibrotic conditions. The purpose of this review is to provide an overview of emerging antifibrotic agents that have shown encouraging results in preclinical or early clinical studies, but have not yet been approved for use in human disease. One of these agents is bone morphogenetic protein-7 (BMP7), which has beneficial effects in multiple models of fibrotic disease. Another approach discussed involves altering the levels of micro-RNA (miR) species, including miR-29 and miR-101, which regulate the expression of fibrosis-related gene targets. Further, the antifibrotic potential of agonists of the peroxisome proliferator-activated receptors (PPARs) will be discussed. Finally, evidence will be reviewed in support of the polypeptide hormone relaxin. Relaxin is long known for its extracellular remodeling properties in pregnancy, and is rapidly emerging as an effective antifibrotic agent in a number of organ systems. Moreover, relaxin has potent vascular and renal effects that make it a particularly attractive approach for the treatment of cardiovascular diseases. In each case, the mechanism of action and the applicability to various fibrotic diseases will be discussed.